Single-shot multi-view imaging enabled by scattering lens - Zhu, Xiangwen (2022)
Imaging three-dimensional (3D) objects has been realized by methods such as binocular stereo vision and multi-view imaging. These methods, however, needs multiple cameras or multiple shots to get elemental images. In this paper, we develop a single-shot multi-view imaging technique by utilizing the natural randomness of scattering media. By exploiting the memory effect and uncorrelated point spread functions (PSF) among scattering media, we demonstrate that both stereo imaging with large disparity and up to seven-view imaging of a 3D object can be reconstructed from only one speckle pattern by deconvolution. The elemental images are consistent with 3D object projection and images taken by multi-shot imaging. Our technique provides a feasible method to capture multi-view imaging with short acquisition time and easy calibration.